Dune Russet: A French-Fry Potato Cultivar with High Specific Gravity under High-Temperature Growing Conditions and Excellent Processing Quality after Long-Term Cold Storage - M. Isabel Vales; Douglas C. Scheuring; Jeffrey W. Koym; Jeewan Pandey; Stephany E. Toinga-Villafuerte; Joshua R. Johnson; Caroline P. Gray; David G. Holm; Mohamad Chikh-Ali; Robert G. Wilson; Richard G. Novy; Jonathan L. Whitworth; et al. (American Journal of Potato Research, 2026)
Dune Russet (COTX08063-2Ru) is the first French fry russet potato cultivar released by the Texas A&M Potato Breeding Program. It derives from a cross made by the Colorado State University Potato Program between Premier Russet and A99073-1 and was subsequently selected and advanced by the Texas Program. Dune Russet has oblong potato tubers with light russet skin texture and white flesh. It is characterized by having excellent French fry quality and cold-induced sweetening resistance, producing light-colored fries directly from the field and even after several months (three to eight) in cold storage at 4.4 °C. Dune Russet is especially recommended for areas that experience high-temperature stress during the growing season, as it can retain high specific gravity near 1.090 and produce light French fries despite heat stress. Across multi-location trials, Dune Russet outperformed the reference cultivar, Russet Burbank, and other processing cultivars in French fry quality, while offering some field-based PVY tolerance and good agronomic performance, including competitive marketable yields and a high proportion of US No. 1 tubers.

A Method to Screen Potato Breeding Lines for Blackheart Resistance - Duroy Navarre; Max Feldman; Vidyasagar Sathuvalli; Brian Charlton; Collins Wakholi; Moehninsi; Asunta Thompson; Jacob Blauer (American Journal of Potato Research, 2026)

Developing Molecular Markers Linked to Corky Ringspot Resistance in Solanum tuberosum - Shengwei Hu; Ryan Graebner; Rich Quick; Noelle L. Anglin; Kylie Swisher Grimm; Max Feldman; Hans-Reinhard Hofferbert; Vidyasagar Sathuvalli (Potato Research, 2025)

A Genome Wide Association Study (GWAS) Identifies SNPs Associated with Resistance to Tobacco Rattle Virus (TRV) and Potato Mop-Top Virus (PMTV) in a Tetraploid Mapping Population of Potato - Noelle L. Anglin; Shashi K. R. Yellarreddygari; Neil C. Gudmestad; Vidyasagar Sathuvalli; Charles R. Brown; Max Feldman; Walter S. De Jong; David S. Douches; Richard G. Novy; Joseph J. Coombs (American Journal of Potato Research, 2024)

Rainier Russet: A Dual Use Russet Potato with Long Tuber Dormancy, Excellent Process Quality, and High Early Harvest Packaging Efficiency - Jacob M. Blauer; Vidyasagar Sathuvalli; Brian A. Charlton; Solomon Yilma; Clint C. Shock; Nicole Baley; Ruijun Qin; Erik Feibert; Richard G. Novy; Jonathan L. Whitworth; Mark J. Pavek; Norman R. Knowles; et al. (American Journal of Potato Research, 2024)
‘Rainier Russet’ was released in 2020 as a medium- to late-maturing selection with russeted tubers. Total yields are less, but similar to controls ‘Ranger Russet’ and ‘Russet Burbank’, and U.S. No. 1 yields are higher than Russet Burbank with increased tubers > 284 g. Compared to controls, it has high protein levels, high specific gravity, excellent fry color and flavor ratings, low acrylamide potential, good post-harvest merit scores for processing quality, and few internal and external tuber defects. Rainier Russet is susceptible to blight diseases, PVY, and Fusarium dry rot ( F. solani var. sambucinum ), but resistant to common scab ( Streptomyces scabies ) and Fusarium dry rot ( F. solani var. coeruleum ). Compared to Russet Burbank, tubers are less susceptible to hollow heart/brown center, secondary growth, growth cracks, and internal brown spot but higher tuber defects for net necrosis and shatter bruise with similar blackspot bruise potential. Rainier Russet is noted for its long tuber dormancy compared to Russet Burbank.

A Canister Assay for Evaluating Host Status of Potato to Meloidogyne Chitwoodi - Michelle Soulé; Megan Kitner; Gabrielle Studebaker; Max J. Feldman; Vidyasagar Sathuvalli; Inga Zasada (American Journal of Potato Research, 2023)

TubAR: an R Package for Quantifying Tuber Shape and Skin Traits from Images - Michael D. Miller; Cari A. Schmitz Carley; Rachel A. Figueroa; Max J. Feldman; Darrin Haagenson; Laura M. Shannon (American Journal of Potato Research, 2023)
Potato market value is heavily affected by tuber quality traits such as shape, color, and skinning. Despite this, potato breeders often rely on subjective scales that fail to precisely define phenotypes. Individual human evaluators and the environments in which ratings are taken can bias visual quality ratings. Collecting quality trait data using machine vision allows for precise measurements that will remain reliable between evaluators and breeding programs. Here we present TubAR (Tuber Analysis in R), an image analysis program designed to collect data for multiple tuber quality traits at low cost to breeders. To assess the efficacy of TubAR in comparison to visual scales, red-skinned potatoes were evaluated using both methods. Broad sense heritability was consistently higher for skinning, roundness, and length to width ratio using TubAR. TubAR collects essential data on fresh market potato breeding populations while maintaining efficiency by measuring multiple traits through one phenotyping protocol.

High-Dose IV Administration of Rasburicase Suppresses Anti-rasburicase Antibodies, Depletes Rasburicase-Specific Lymphocytes, and Upregulates Treg Cells - Hui Xu; Gerald M. Feldman; Edward E. Max (The AAPS Journal, 2020)